Conservative versus surgical treatment of metacarpal and metatarsal fractures in dogs - Kapatkin, A.; Howe-Smith, R.; Shofer, F. (Veterinary and Comparative Orthopaedics and Traumatology, 2000)
The purpose of this retrospective study was to compare the outcome of metacarpal and metatarsal fractures treated conservatively versus surgically. Internal fixation of these fractures is recommended if there are: more than two metacarpal or metatarsal fractures in the same leg; two fractures of weight bearing bones; articular fractures; fractures with significant displacement; open fractures; and if the fractures occur in large breed, athletic, show, or working dogs. All 25 dogs fit the published criteria for surgical fixation to achieve a good outcome. Treatment (surgical versus conservative) was assigned based on owners’ decisions only. Follow-up was nine-68 months. Anything less than perfect in the categories used to evaluate outcome was considered a failure. Outcome was not statistically affected by surgery or conservative treatment, and no other factors significantly affected outcome. The present recommendations used in determining if surgery is necessary for these fractures were extrapolated from human literature and may have no scientific validity in our patients.Open reduction and fixation was compared with closed reduction and coaptation for the treatment of multiple fractures of the metacarpal and metatarsal bones in 25 dogs.
Keywords: Metacarpal fractures; metatarsal fractures; canine; treatment outcome